Green Buildings and Smart Houses - The Measurement of Sustainable Return with SROI - Pintér, Éva; Bagó, Péter (The Hungarian Journal of Marketing and Management, 2019)
The enormous economic growth requirements and the pressure on people to increase consumption lead to high energy expenditure and energy waste. There is a transformational period and in this paper we seek a connection between traditional analysis, new dynamic measurements of energy use and waste and the triple bottom line including the social, environmental and economic attributes of a building. Traditional life cycle analysis techniques focus on direct cash benefits, but Sustainable Return on Investment or SROI is a process through which direct cash, noncash and external costs and benefits can be calculated and presented in monetary terms.